From fields to strings:circumnavigating theoritical physics - From fields to strings; Vainshtein Arkady , ed. (World Scientific, 2005)
This volume is a collection of dedicated reviews covering all aspects of theoretical high energy physics and some aspects of solid state physics. Some of the papers are broad reviews of topics that span the entire field while others are surveys of authors' personal achievements. This is the most comprehensive review collection reflecting state of the art at the end of 2004. An important and unique aspect is a special effort the authors have invested in making the presentation pedagogical.
Keywords: Nuclear physics